Consumption experience, choice experience and the endowment effect - Steven J. Humphrey; Luke Lindsay; Chris Starmer (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
This paper reports an experiment investigating how different kinds of experience influence the endowment effect. Previous studies have investigated how the endowment effect is influenced by experience gained through repetition of decision problems and trading in natural and experimental markets. In this study we explore how it is influenced by experience of consuming elements of a potential endowment and by experience of choosing prior to acquiring an endowment. We find evidence of an endowment effect and that measured loss aversion predicts the reluctance to trade. We find no effect of consumption experience. Choice experience increases trading. Finally, we find evidence of a new species of 'splitting effect', whereby acquiring an endowment in two instalments significantly reduces trading.
Keywords: C91; D12; 330; endowment effect; experience; splitting effects